Neoantigens and NK Cells: “Trick or Treat” the Cancers? - Lv, Dan; Khawar, Muhammad Babar; Liang, Zhengyan; Gao, Yu; Sun, Haibo (Frontiers in Immunology, 2022)
Immunotherapy has become an important treatment strategy for cancer patients nowadays. Targeting cancer neoantigens presented by major histocompatibility complex (MHC) molecules, which emerge as a result of non-synonymous somatic mutations with high immunogenicity, is one of the most promising cancer immunotherapy strategies. Currently, several therapeutic options based on the personalized or shared neoantigens have been developed, including neoantigen vaccine and adoptive T cell therapy, both of which are now being tested in clinical trials for various malignancies. The goal of this review is to outline the use of neoantigens as cancer therapy targets, with an emphasis on neoantigen identification, clinical usage of personalized neoantigen-based cancer therapy agents, and the development of off-the-shelf products based on shared neoantigens. In addition, we introduce and discuss the potential impact of the neoantigen-MHC complex on natural killer (NK) cell anti-tumor function, which could be a novel way to boost immune response induced cytotoxicity against malignancies.